What Is “Natural”? Consumer Responses to Selected Ingredients - Chambers, Edgar, V; Chambers, Edgar, IV; Castro, Mauricio (My University, 2018)
Interest in “natural” food has grown enormously over the last decade. Because the United States government has not set a legal definition for the term “natural”, customers have formed their own sensory perceptions and opinions on what constitutes natural. In this study, we examined 20 ingredients to determine what consumers consider to be natural. Using a national database, 630 consumers were sampled (50% male and 50% female) online, and the results were analyzed using percentages and chi-square tests. No ingredient was considered natural by more than 69% of respondents. We found evidence that familiarity may play a major role in consumers’ determination of naturalness. We also found evidence that chemical sounding names and the age of the consumer have an effect on whether an ingredient and potentially a food is considered natural. Interestingly, a preference towards selecting GMO (genetically modified organisms) foods had no significant impact on perceptions of natural.
Citation: Chambers, E., Chambers, E., & Castro, M. (2018). What Is “Natural”? Consumer Responses to Selected Ingredients. Foods, 7(4), 65. https://doi.org/10.3390/foods7040065
Keywords: Consumer; Ingredient; Natural; Perception